Challenges and Impact of Globalization on Indian Economy: The Role and Relevance in Indian Economy - Agarwal, Hari Om (Journal of Commerce and Trade, 2007)
The world has become a small village, thanks to the rapid means of transportation and telecommunications. Satellite transmission has widened the geographical markets. The countries have become interdependent in terms of technology, capital, purchases and sales. Global companies buy from the cheapest markets and sell where they can get maximum prices i.e. globalization calls for reduction of costs, improvement of quality , expansion of markets and diversification into new areas and market. Indian companies use not only imported components but are also selling their finished products to market abroad. To take advantage of global markets, Indian companies are making strategic alliances with foreign companies. The most successful companies will rely more and more on global integration and networking.